Utopia and Terror in Contemporary American Fiction. - Newman, Judie (Routledge transnational perspectives on American literature., 2014)
This book examines the quest for/failure of Utopia across a range of contemporary American/transnational fictions in relation to terror and globalization through authors such as Susan Choi, André Dubus, Dalia Sofer, and John Updike. While recent critical thinkers have reengaged with Utopia, the possibility of terror - whether state or non-state, external or homegrown - shadows Utopian imaginings. Terror and Utopia are linked in fiction through the exploration of the commodification of affect, a phenomenon of a globalized world in which feelings are managed, homogenized across cultures, exag.